Assessment of energy efficiency investment in Onitsha business cluster, Nigeria - Stephen Kelechi Dimnwobi; Ebele Stella Nwokoye; Clement Izuchukwu Igbanugo; Chukwunonso Ekesiobi; Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
This paper empirically assesses energy efficiency (EE) adoption among firms by examining the factors that drive investment in energy efficiency in the Onitsha plastic cluster, South-East, Nigeria. Self-administered questionnaires were delivered to the selected enterprises. A total of 450 questionnaires were administered of which 423 were certified valid and utilized for the analysis. A Heckit model was developed and estimated. Gender, firm size, Joneses effect, and expected cost reduction benefits are the significant determinants of energy efficiency investment. However, firm structure, government incentives, regulatory requirements, and reduction of carbon emission are insignificant drivers of EE investment decisions in the Onitsha Plastic Cluster. This paper presents a foremost attempt at analysing the determinants of energy investment in a cluster in Nigeria.
Keywords: 330; Energy Efficiency; Nigeria; Onitsha; Plastic; Cluster